Preparation method and application of polymer copper powder mixed core solder ball

By mixing conductive polymer with copper powder and preparing mixed core microspheres using ultrasonic spray technology, and then forming a multi-layer structure through electroplating, the lack of performance of traditional solder balls under the trend of miniaturization and high performance of electronic devices is solved, and the high conductivity, mechanical strength and long-term reliability of solder balls are achieved.

CN119772447APending Publication Date: 2025-04-08SHANGHAI TINKING MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510136020.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Under the trend of miniaturization and high performance of electronic devices, traditional solder balls face challenges in conductive properties, mechanical properties and thermal stability, and the solder joint stress relief ability is insufficient, which affects the reliability and durability of solder balls.

Method used

The preparation method of polymer copper powder mixed core solder balls is adopted. By mixing conductive polymer with copper powder and ultrasonic spraying technology, mixed core microspheres are prepared, and then transition metal layer and alloy layer are formed on the surface through electroplating to improve the conductivity, mechanical properties and connection properties of the solder balls.

Benefits of technology

The excellent conductivity and mechanical strength of the solder ball are achieved, and stable performance can be maintained in high temperature and high frequency environments, improve the reliability and durability of the solder ball, and enhance the stability and connection strength of the solder ball.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005263235360000131
    Figure BDA0005263235360000131
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a polymer copper powder mixed core solder ball, and belongs to the technical field of solder balls. According to the invention, the conductive polymer and the copper powder are mixed, the mixed core microsphere with excellent performance is prepared by using an ultrasonic spraying method, and then a transition metal layer and an alloy layer are arranged on the surface of the mixed core microsphere in an electroplating manner, so that the polymer and copper powder mixed core solder ball with excellent conductivity and mechanical performance is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solder balls, and relates to a preparation method and application of a polymer copper powder mixed core solder ball. Background Art

[0002] In the field of modern electronic packaging, solder balls, as key components connecting chips and substrates, are not only simple connecting elements, but also the key link to ensure the performance and reliability of electronic equipment. Traditionally, solder balls are mainly made of metal materials, such as tin alloys, to achieve electrical signal transmission and mechanical support. However, with the continuous miniaturization and high performance of electronic devices, the challenges faced by traditional solder balls are becoming increasingly prominent. With the trend of shrinking electronic devices, the size of solder balls is also decreasing, which puts higher requirements on the conductivity and mechanical properties of solder ball materials. In addition, with the continuous increase in the operating frequency of electronic devices, solder balls not only need to have excellent conductivity, but also need to be able to maintain stable electrical properties at high frequencies. At the same time, the high temperature working environment of electronic devices also puts higher requirements on the thermal stability of solder balls. In addition, the solder joints need to have a certain degree of relief ability for the generated stress, thereby reducing the risk of cracking at the connection.

[0003] Conductive polymers, as a new type of solder ball core material, have gradually attracted attention due to their excellent conductivity, thermal stability and mechanical properties. Poly(3,4-ethylenedithiophene):poly(styrene sulfonate) (PEDOT:PSS) is a typical conductive polymer with good properties mentioned above and has broad application prospects in the field of electronic devices. However, a single conductive polymer solder ball may have problems with insufficient mechanical properties and conductivity, which is not conducive to the reliability and durability of the solder ball.

[0004] In order to solve the above problems, this paper proposes a new method for preparing polymer / copper powder mixed core solder balls, in which conductive polymers are mixed with copper powders, and a mixed core solder ball with excellent performance is prepared by ultrasonic spraying. This method can not only maintain the conductivity and thermal stability of the solder ball, but also enhance the mechanical and elastic properties of the solder ball, thereby improving the reliability and durability of the solder ball. At the same time, the outer transition metal layer (Cu, Ni, Ag, etc.) and solder layer (Sn alloy, etc.) are prepared by chemical deposition or electroplating, which further improves the connection performance of the solder ball.

[0005] This new type of polymer / copper powder mixed core solder ball has a wide range of application prospects in the field of electronic packaging. It can not only be applied to traditional welding technology, but also to more demanding electronic device packaging, such as BGA packaging. By optimizing the preparation process and material formulation, this hybrid core solder ball is expected to become one of the important innovations in the field of electronic packaging in the future. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation method and application of a polymer copper powder mixed core solder ball. The polymer copper powder mixed core solder ball prepared by the present invention has excellent conductivity and mechanical strength, and after passing 200 thermal cycle tests, the conductivity and mechanical strength of the solder ball remain within a stable range.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing a polymer copper powder mixed core solder ball comprises the following preparation steps:

[0009] S1. Preparation of mixed solution:

[0010] Dissolving poly(3,4-ethylenedioxythiophene) and poly(styrene sulfonic acid) in a mass ratio of 1:1 in acetonitrile to prepare a conductive polymer solution with a concentration of 5-10wt%, dispersing nano copper powder in the solution to form a copper powder suspension, wherein the mass ratio of nano copper powder to deionized water in the copper powder suspension is 1:(15-30), and fully stirring the conductive polymer solution and the copper powder suspension in a volume ratio of 1:(1-2) to obtain a mixed solution;

[0011] S2. Preparation of polymer / copper powder core microspheres:

[0012] The mixed solution is placed in an ultrasonic atomizer, and the solution is atomized into tiny droplets by the action of ultrasound to form polymer / copper powder mixed core microspheres, wherein the ultrasonic spraying conditions are as follows: temperature 45-55° C., time 10-15 min, power 100-110 W, and the polymer / copper powder mixed core microspheres are prepared after complete drying and curing;

[0013] S3, activation treatment:

[0014] The prepared polymer / copper powder mixed core microspheres are finely polished, then rinsed with distilled water, and then placed in a constant temperature alkaline washing solution of 55°C, taken out after 3-5 minutes and rinsed with distilled water to obtain a deoiled solid A; solid A is placed in an acid solution and soaked for 40-60 seconds, and then rinsed with distilled water to obtain an acid-washed solid B; solid B is placed in an activation solution for 5 minutes to obtain a surface-activated polymer / copper powder mixed core microsphere, wherein the concentration of potassium phosphate in the activation solution is 110 g / L, the concentration of phosphoric acid is 100 mg / L, the concentration of sodium fluoride is 20 g / L, and the concentration of sodium dodecyl sulfate is 100 mg / L;

[0015] S4, polymer / copper powder core microsphere surface treatment:

[0016] S4.1, immersing the surface activated polymer / copper powder mixed core microspheres in a plating solution A containing nickel ions, and electroplating to form a nickel layer on the surface of the microspheres, wherein the nickel ion concentration in the plating solution A is 20-25 g / L, the boric acid concentration is 20-25 g / L, and the hypophosphite ion concentration is 8-12 g / L;

[0017] S4.2, continue to immerse the polymer / copper powder core microspheres obtained in step S4.1 into the electroplating solution B containing silver ions at a current density of 1 to 10 A / dm 2 A silver layer is formed by electroplating under the conditions of

[0018] S4.3, immerse the polymer / copper powder core microspheres obtained in step S4.3 in a solution containing electroplating solution C at a current density of 3 to 5 A / dm 2 A Sn-Ag-Cu alloy layer is formed by electroplating under the conditions of, wherein the concentration of stannous methanesulfonate in the electroplating solution C is 0.2 mol / L, the concentration of copper methanesulfonate is 1.5 mmol / L, the concentration of silver methanesulfonate is 4.5 mmol / L, the concentration of sodium citrate is 0.45 mol / L, the concentration of ethylenediaminetetraacetic acid is 0.375 mol / L, the concentration of ascorbic acid is 1 g / L, the concentration of thiourea is 0.6 mol / L, the concentration of modified graphene is 0.2-0.5 g / L, and the concentration of the dispersant is 10-20 g / L;

[0019] S5. Cleaning and drying:

[0020] The electroplated polymer / copper powder core microspheres were washed with deionized water and dried at 105° C. for 8 to 14 hours to prepare polymer copper powder mixed core solder balls.

[0021] As a preferred technical solution of the present invention, in step S3, the components of the constant temperature alkaline washing solution are NaOH, sodium carbonate, sodium phosphate and pure water in a mass ratio of 3:1:3:50.

[0022] As a preferred technical solution of the present invention, in step S3, the acid solution is a nitric acid solution with a concentration of 30 ml / L.

[0023] As a preferred technical solution of the present invention, in step S4.1, the current density during electroplating is 3 to 7 A / dm 2 The electroplating time is 5 to 10 minutes and the temperature is 25 to 50°C.

[0024] As a preferred technical solution of the present invention, in step S4.2, the silver ion concentration in the electroplating solution B is 10-15 g / L, and the boric acid concentration is 20-30 g / L.

[0025] As a preferred technical solution of the present invention, in step S4.2, the electroplating time is 3 to 6 minutes.

[0026] As a preferred technical solution of the present invention, in step S4.3, the preparation process of the modified graphene is as follows:

[0027] At 40-45° C., graphene, N-ethylpyridinium tetrafluoroborate and ethanol in a mass ratio of (1-3): (10-15): 50 are uniformly mixed, and ultrasonic treatment is performed for 35-50 minutes. After the ultrasonic treatment, the precipitate is centrifuged and washed with deionized water, and vacuum dried at 95° C. for 6-10 hours to obtain modified graphene.

[0028] As a preferred technical solution of the present invention, in step S4.3, the dispersant is cetearyl alcohol polyether and sodium hexadecyl sulfate in a mass ratio of 1:1.

[0029] As a preferred technical solution of the present invention, in step S4.3, the current density during electroplating is 2.5 to 3.5 A / dm 2 The electroplating time is 3 to 5 minutes and the temperature is 25 to 40°C.

[0030] The invention discloses an application of a polymer copper powder mixed core solder ball, wherein the polymer copper powder mixed core solder ball can be applied to traditional welding technology and the field of electronic device packaging.

[0031] In the present invention, a conductive polymer and copper powder are mixed, wherein the conductive polymer is poly(3,4-ethylenedithiophene) and poly(styrene sulfonic acid). This material can maintain stable conductive properties under long-term working conditions, and due to its mechanical toughness, it can show excellent durability under high temperature and high frequency environments. Mixing with copper powder can solve the problems of insufficient mechanical properties and conductive properties of a single conductive polymer solder ball, and avoid affecting the reliability and durability of the solder ball.

[0032] At the same time, ultrasonic spray technology is used to prepare mixed core solder balls with excellent performance. The temperature is controlled at 45-55°C to prevent the polymer solution from degrading due to high temperature and ensure the chemical stability during the atomization process. At the same time, the ultrasonic power of 100-110W can provide enough energy to atomize the solution into the required tiny droplets, which helps to control the final particle size of the solder balls. Ultrasonic spray technology can generate high-quality solder balls with high efficiency, ensuring the uniformity of size and performance consistency of each solder ball, which is crucial for large-scale production and application.

[0033] The prepared polymer / copper powder mixed core microspheres can not only maintain the electrical conductivity and thermal stability of the solder balls, but also enhance the mechanical properties and elastic properties of the solder balls, thereby improving the reliability and durability of the solder balls.

[0034] At the same time, the transition metal layer and alloy layer are coated on the outside of the polymer / copper powder mixed core microsphere by electroplating, which can further improve the connection performance of the solder ball. The polymer / copper powder mixed core microsphere is activated before electroplating, and the surface of the polymer / copper powder mixed core microsphere is polished, alkaline washed, and acid washed in turn to improve the quality and performance of the electroplating layer. These pretreatment steps can remove impurities such as defects, oil stains, oxides, etc. on the metal surface, improve the surface roughness, and provide a cleaner and more suitable surface condition for the adhesion of the electroplating layer.

[0035] At the same time, in order to further promote the good combination of the subsequent electroplating layer and the polymer / copper powder mixed core microspheres, the activated liquid is used for treatment. The metal surface after activation treatment is easier to be infiltrated and adsorbed by the electroplating liquid, thereby improving the adhesion between the electroplating layer and the metal substrate.

[0036] The potassium phosphate and phosphoric acid components in the activation solution help to form a phosphating film on the metal surface. This phosphating film can serve as a transition layer between the electroplating layer and the metal substrate, further improving the adhesion and corrosion resistance of the electroplating layer. The presence of sodium fluoride helps to reduce the temperature of the phosphating film formation, which is conducive to the formation of a crystalline and dense conversion film. The sodium dodecyl sulfate surfactant can improve the wettability and dispersibility of the activation solution, making it easier for the activation solution to penetrate into the tiny pores and cracks on the metal surface, thereby improving the activation effect, improving the wettability of the solution to the metal surface, and helping the activation solution to better contact and react with the metal surface.

[0037] After activation, the surface is coated with a nickel layer, a silver layer, and a Sn-Ag-Cu alloy layer in sequence, wherein modified graphene is added to the Sn-Ag-Cu alloy layer. Graphene itself has excellent electrical conductivity, and after being modified by ionic liquid, the electrical conductivity of the electroplating solution can be further improved, which helps to improve the current efficiency and electroplating speed during the electroplating process, thereby shortening the electroplating time. Graphene modified by ionic liquid can be evenly dispersed in the electroplating solution, thereby forming a more uniform coating during the electroplating process, which helps to reduce defects and pores in the coating and improve the density and adhesion of the coating.

[0038] The addition of graphene can significantly improve the hardness and wear resistance of the coating. Graphene has excellent thermal stability, and its addition can further improve the thermal stability of Sn-Ag-Cu alloy, allowing it to maintain stable performance in high temperature environments. At the same time, the excellent conductivity of graphene helps to form a more uniform conductive network in the alloy, thereby improving the conductivity of the alloy to a certain extent.

[0039] At the same time, cetyl stearyl alcohol polyether and sodium hexadecyl sulfonate in a mass ratio of 1:1 are added to the electroplating solution. The molecular structure of sodium hexadecyl sulfonate contains long-chain alkyl and sulfonate ions. This type of dispersant has good water solubility and dispersibility, which can effectively reduce the surface tension in the electroplating solution and make the metal ions more evenly distributed in the solution. At the same time, they can also form stable complexes with metal ions to prevent metal ions from agglomerating or precipitating during the electroplating process. Polyether dispersants can significantly improve the dispersion stability of tiny particles in the electroplating solution, thereby improving the gloss and fineness of the coating. After being mixed with sodium hexadecyl sulfonate as a dispersant in the electroplating solution, cetyl stearyl alcohol polyether has significant dispersing, wetting, stabilizing and synergistic effects, significantly reducing the surface tension of solid particles in the electroplating solution, and can significantly improve the electroplating efficiency and coating quality.

[0040] Beneficial effects of the present invention:

[0041] (1) The present invention prepares a mixed core microsphere with excellent performance by mixing a conductive polymer with copper powder using an ultrasonic spray method, and then prepares a polymer copper powder mixed core solder ball with excellent conductivity and mechanical properties by electroplating a transition metal layer and an alloy layer on the surface.

[0042] (2) By sequentially depositing a nickel layer, a silver layer, and a Sn-Ag-Cu alloy layer on the outside of the hybrid core microsphere, multiple improvements in conductivity, mechanical properties, and welding reliability can be achieved. The nickel layer provides anti-oxidation protection, effectively preventing the solder ball from oxidizing in a humid environment and extending its service life. The silver layer improves conductivity and can improve the electrical performance of the solder ball. The Sn-Ag-Cu alloy layer ensures the stability of the welding process. The multi-layer structure design enables welding in the outer layer design, which can achieve multiple improvements in conductivity, mechanical properties, and welding reliability. The multi-layer structure design enables the solder ball to maintain excellent performance in complex environments such as high temperature, high humidity, and high mechanical stress, and is suitable for packaging applications with higher requirements for long-term reliability, such as automotive electronics and industrial control systems. This multi-layer structure design can effectively solve the problem of unstable performance of single-layer solder balls under extreme conditions, thereby improving the reliability and life of solder balls in practical applications.

[0043] Using Sn-Ag-Cu (SAC) alloy as the solder layer can significantly improve the soldering performance of the solder ball. The SAC alloy layer has good thermal fatigue resistance, exhibits excellent wettability during high-temperature soldering, and can form a stable solder connection at the soldering point. The use of this solder can enhance the connection strength between the solder ball and the substrate and reduce the risk of loosening or breaking of the solder joint under high temperature conditions. In addition, the SAC solder layer can also effectively improve the thermal aging resistance of the solder ball, ensuring that it can be used for a long time in a high-temperature environment without performance degradation. This is of great significance for high-temperature electronic packaging applications, especially in automotive electronics and industrial control devices. DETAILED DESCRIPTION

[0044] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0045] In the following examples and comparative examples:

[0046] Poly(3,4-ethylenedioxythiophene): purchased from Hefei Ruikesheng Biotechnology Co., Ltd.; poly(styrene sulfonic acid): purchased from Shanghai Yien Chemical Technology Co., Ltd., product number: R054783; graphene: purchased from Suzhou Qingtan Nanomaterials Co., Ltd.; N-ethylpyridinium tetrafluoroborate: purchased from Shenyang Deyuan Tianhai Biotechnology Co., Ltd.; cetearyl alcohol polyether: purchased from Jiangsu Xinyu Biotechnology Co., Ltd.; sodium hexadecyl sulfonate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: S857449.

[0047] Example 1

[0048] S1. Preparation of mixed solution:

[0049] Dissolving poly(3,4-ethylenedioxythiophene) and poly(styrene sulfonic acid) in a mass ratio of 1:1 in acetonitrile to prepare a conductive polymer solution with a concentration of 5 wt%, dispersing nano copper powder in the solution to form a copper powder suspension, wherein the mass ratio of nano copper powder to deionized water in the copper powder suspension is 1:15, and fully stirring the conductive polymer solution and the copper powder suspension in a volume ratio of 1:1 to obtain a mixed solution;

[0050] S2. Preparation of polymer / copper powder core microspheres:

[0051] The mixed solution is placed in an ultrasonic atomizer, and the solution is atomized into tiny droplets by the action of ultrasound to form polymer / copper powder mixed core microspheres, wherein the ultrasonic spray condition parameters are temperature 45° C., time 10 min, power 100 W, and the polymer / copper powder mixed core microspheres are prepared after complete drying and curing;

[0052] S3, activation treatment:

[0053] The prepared polymer / copper powder mixed core microspheres were finely polished, then rinsed with distilled water, and then placed in a constant temperature alkaline washing solution of 55°C, taken out and rinsed with distilled water after 3 minutes to obtain a deoiled solid A, wherein the components of the constant temperature alkaline washing solution are NaOH, sodium carbonate, sodium phosphate and pure water in a mass ratio of 3:1:3:50; solid A was placed in a nitric acid solution with a concentration of 30 ml / L and soaked for 40 to 60 seconds, and then continued to be rinsed with distilled water to obtain a solid B after acid washing; solid B was placed in an activation solution for 5 minutes to obtain a surface-activated polymer / copper powder mixed core microsphere, wherein the concentration of potassium phosphate in the activation solution is 110 g / L, the concentration of phosphoric acid is 100 mg / L, the concentration of sodium fluoride is 20 g / L, and the concentration of sodium dodecyl sulfate is 100 mg / L;

[0054] S4, polymer / copper powder core microsphere surface treatment:

[0055] S4.1. Immerse the surface activated polymer / copper powder mixed core microspheres in a plating solution A containing nickel ions, and electroplate a nickel layer on the surface of the microspheres. The nickel ion concentration in the plating solution A is 20 g / L, the boric acid concentration is 20 g / L, the hypophosphite ion concentration is 8 g / L, and the current density during electroplating is 3 A / dm 2 , the electroplating time is 5min, the temperature is 25℃;

[0056] S4.2, continue to immerse the polymer / copper powder core microspheres obtained in step S4.1 into the electroplating solution B containing silver ions at a current density of 1A / dm 2 The silver layer is formed by electroplating under the conditions of: the silver ion concentration in the electroplating solution B is 15 g / L, the boric acid concentration is 30 g / L, and the electroplating time is 6 min;

[0057] S4.3, the preparation process of modified graphene is as follows:

[0058] At 45°C, graphene, N-ethylpyridinium tetrafluoroborate and ethanol in a mass ratio of 1:10:50 were mixed evenly, and ultrasonically treated for 35 minutes. After the ultrasonic treatment, the precipitate was centrifuged and washed with deionized water, and vacuum dried at 95°C for 6 hours to obtain modified graphene.

[0059] The polymer / copper powder core microspheres obtained in step S4.3 are immersed in the electroplating solution C at a current density of 3 A / dm 2The Sn-Ag-Cu alloy layer is formed by electroplating under the conditions of , wherein the concentration of stannous methanesulfonate in the electroplating solution C is 0.2 mol / L, the concentration of copper methanesulfonate is 1.5 mmol / L, the concentration of silver methanesulfonate is 4.5 mmol / L, the concentration of sodium citrate is 0.45 mol / L, the concentration of ethylenediaminetetraacetic acid is 0.375 mol / L, the concentration of ascorbic acid is 1 g / L, the concentration of thiourea is 0.6 mol / L, the concentration of modified graphene is 0.2 g / L, the concentration of dispersant is 10 g / L, the dispersant is cetyl stearyl alcohol polyether and sodium hexadecyl sulfate in a mass ratio of 1:1, and the current density during electroplating is 2.5 A / dm 2 , the electroplating time is 3min, the temperature is 25℃;

[0060] S5. Cleaning and drying:

[0061] The electroplated polymer / copper powder core microspheres were washed with deionized water and dried at 105° C. for 8 h to prepare polymer copper powder mixed core solder balls.

[0062] Example 2

[0063] S1. Preparation of mixed solution:

[0064] Dissolving poly(3,4-ethylenedioxythiophene) and poly(styrene sulfonic acid) in a mass ratio of 1:1 in acetonitrile to prepare a conductive polymer solution with a concentration of 8 wt%, dispersing nano copper powder in the solution to form a copper powder suspension, wherein the mass ratio of nano copper powder to deionized water in the copper powder suspension is 1:22, and fully stirring the conductive polymer solution and the copper powder suspension in a volume ratio of 1:1.5 to obtain a mixed solution;

[0065] S2. Preparation of polymer / copper powder core microspheres:

[0066] The mixed solution is placed in an ultrasonic atomizer, and the solution is atomized into tiny droplets by the action of ultrasound to form polymer / copper powder mixed core microspheres, wherein the ultrasonic spray condition parameters are temperature 50° C., time 13 min, power 105 W, and the polymer / copper powder mixed core microspheres are prepared after complete drying and curing;

[0067] S3, activation treatment:

[0068] The prepared polymer / copper powder mixed core microspheres were finely polished, then rinsed with distilled water, and then placed in a constant temperature alkaline washing solution of 55°C, taken out and rinsed with distilled water after 4 minutes to obtain a deoiled solid A, wherein the components of the constant temperature alkaline washing solution are NaOH, sodium carbonate, sodium phosphate and pure water in a mass ratio of 3:1:3:50; solid A was placed in a nitric acid solution with a concentration of 30 ml / L and soaked for 50 seconds, and then continued to be rinsed with distilled water to obtain a solid B after acid washing; solid B was placed in an activation solution for 5 minutes to obtain a surface-activated polymer / copper powder mixed core microsphere, wherein the concentration of potassium phosphate in the activation solution is 110 g / L, the concentration of phosphoric acid is 100 mg / L, the concentration of sodium fluoride is 20 g / L, and the concentration of sodium dodecyl sulfate is 100 mg / L;

[0069] S4, polymer / copper powder core microsphere surface treatment:

[0070] S4.1. Immerse the surface activated polymer / copper powder mixed core microspheres in electroplating solution A containing nickel ions, and electroplate a nickel layer on the surface of the microspheres. The nickel ion concentration in the electroplating solution A is 22 / L, the boric acid concentration is 23 / L, the hypophosphite ion concentration is 10g / L, and the current density during electroplating is 5A / dm 2 , the electroplating time is 7min, the temperature is 40℃;

[0071] S4.2, continue to immerse the polymer / copper powder core microspheres obtained in step S4.1 into the electroplating solution B containing silver ions at a current density of 5A / dm 2 The silver layer is formed by electroplating under the conditions of: the silver ion concentration in the electroplating solution B is 13 g / L, the boric acid concentration is 25 g / L, and the electroplating time is 4 min;

[0072] S4.3, the preparation process of modified graphene is as follows:

[0073] At 43°C, graphene, N-ethylpyridinium tetrafluoroborate and ethanol in a mass ratio of 2:12:50 were mixed evenly and ultrasonically treated for 40 minutes. After the ultrasonic treatment, the mixture was centrifuged, washed with deionized water, and vacuum dried at 95°C for 8 hours to obtain modified graphene.

[0074] The polymer / copper powder core microspheres obtained in step S4.3 are immersed in the electroplating solution C at a current density of 4 A / dm 2The Sn-Ag-Cu alloy layer is formed by electroplating under the conditions of , wherein the concentration of stannous methanesulfonate in the electroplating solution C is 0.2 mol / L, the concentration of copper methanesulfonate is 1.5 mmol / L, the concentration of silver methanesulfonate is 4.5 mmol / L, the concentration of sodium citrate is 0.45 mol / L, the concentration of ethylenediaminetetraacetic acid is 0.375 mol / L, the concentration of ascorbic acid is 1 g / L, the concentration of thiourea is 0.6 mol / L, the concentration of modified graphene is 0.3 g / L, the concentration of dispersant is 15 g / L, the dispersant is cetyl stearyl alcohol polyether and sodium hexadecyl sulfate in a mass ratio of 1:1, and the current density during electroplating is 3 A / dm 2 , the electroplating time is 4min, the temperature is 30℃;

[0075] S5. Cleaning and drying:

[0076] The electroplated polymer / copper powder core microspheres were washed with deionized water and dried at 105° C. for 10 h to prepare polymer copper powder mixed core solder balls.

[0077] Example 3

[0078] S1. Preparation of mixed solution:

[0079] Dissolving poly(3,4-ethylenedioxythiophene) and poly(styrene sulfonic acid) in a mass ratio of 1:1 in acetonitrile to prepare a conductive polymer solution with a concentration of 10 wt%, dispersing nano copper powder in the solution to form a copper powder suspension, wherein the mass ratio of nano copper powder to deionized water in the copper powder suspension is 1:30, and fully stirring the conductive polymer solution and the copper powder suspension in a volume ratio of 1:2 to obtain a mixed solution;

[0080] S2. Preparation of polymer / copper powder core microspheres:

[0081] The mixed solution is placed in an ultrasonic atomizer, and the solution is atomized into tiny droplets by the action of ultrasound to form polymer / copper powder mixed core microspheres, wherein the ultrasonic spray condition parameters are a temperature of 55° C., a time of 15 min, and a power of 110 W, and the polymer / copper powder mixed core microspheres are prepared after complete drying and curing;

[0082] S3, activation treatment:

[0083] The prepared polymer / copper powder mixed core microspheres were finely polished, then rinsed with distilled water, and then placed in a 55°C constant temperature alkaline washing solution. After 5 minutes, the microspheres were taken out and rinsed with distilled water to obtain a deoiled solid A, wherein the components of the constant temperature alkaline washing solution were NaOH, sodium carbonate, sodium phosphate and pure water in a mass ratio of 3:1:3:50; solid A was placed in a 30ml / L nitric acid solution and soaked for 60s, and then continued to be rinsed with distilled water to obtain an acid-washed solid B; solid B was placed in an activation solution for 5 minutes to obtain a surface-activated polymer / copper powder mixed core microsphere, wherein the concentration of potassium phosphate in the activation solution was 110g / L, the concentration of phosphoric acid was 100mg / L, the concentration of sodium fluoride was 20g / L, and the concentration of sodium dodecyl sulfate was 100mg / L;

[0084] S4, polymer / copper powder core microsphere surface treatment:

[0085] S4.1. Immerse the surface activated polymer / copper powder mixed core microspheres in a plating solution A containing nickel ions, and electroplate a nickel layer on the surface of the microspheres. The nickel ion concentration in the plating solution A is 25 g / L, the boric acid concentration is 25 g / L, the hypophosphite ion concentration is 12 g / L, and the current density during electroplating is 7 A / dm 2 , the electroplating time is 10min, the temperature is 50℃;

[0086] S4.2, continue to immerse the polymer / copper powder core microspheres obtained in step S4.1 into the electroplating solution B containing silver ions at a current density of 10A / dm 2 The silver layer is formed by electroplating under the conditions of: the silver ion concentration in the electroplating solution B is 10 g / L, the boric acid concentration is 20 g / L, and the electroplating time is 3 min;

[0087] S4.3, the preparation process of modified graphene is as follows:

[0088] At 45°C, graphene, N-ethylpyridinium tetrafluoroborate and ethanol in a mass ratio of 3:15:50 were mixed evenly, and ultrasonically treated for 50 minutes. After the ultrasonic treatment, the precipitate was centrifuged and washed with deionized water, and vacuum dried at 95°C for 10 hours to obtain modified graphene.

[0089] The polymer / copper powder core microspheres obtained in step S4.3 are immersed in the electroplating solution C at a current density of 5 A / dm 2The Sn-Ag-Cu alloy layer is formed by electroplating under the conditions of , wherein the concentration of stannous methanesulfonate in the electroplating solution C is 0.2 mol / L, the concentration of copper methanesulfonate is 1.5 mmol / L, the concentration of silver methanesulfonate is 4.5 mmol / L, the concentration of sodium citrate is 0.45 mol / L, the concentration of ethylenediaminetetraacetic acid is 0.375 mol / L, the concentration of ascorbic acid is 1 g / L, the concentration of thiourea is 0.6 mol / L, the concentration of modified graphene is 0.5 g / L, the concentration of dispersant is 20 g / L, the dispersant is cetyl stearyl alcohol polyether and sodium hexadecyl sulfate in a mass ratio of 1:1, and the current density during electroplating is 3.5 A / dm 2 , the electroplating time is 5min, the temperature is 40℃;

[0090] S5. Cleaning and drying:

[0091] The electroplated polymer / copper powder core microspheres were washed with deionized water and dried at 105° C. for 14 h to prepare polymer copper powder mixed core solder balls.

[0092] Comparative Example 1

[0093] The difference between Comparative Example 1 and Example 1 is that in step S4.3 of Comparative Example 1, the graphene is not modified, and the other operations are the same.

[0094] Comparative Example 2

[0095] The difference between Comparative Example 2 and Example 1 is that in step S4.3 of Comparative Example 2, no modified graphene is added, and the other operations are the same.

[0096] Performance Test:

[0097]

[0098] According to the above data, the polymer copper powder mixed core solder ball prepared by the present invention has excellent conductivity and mechanical strength, and after 200 thermal cycle tests, the conductivity and mechanical strength of the solder ball remain within a stable range without significant performance degradation. This shows that the solder ball has good durability and welding reliability in a high temperature and high frequency environment, and can meet the high requirements of modern electronic packaging for long-term reliability of solder joints.

[0099] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a polymer copper powder mixed core solder ball, characterized in that: The method comprises the following preparation steps: S1. Preparation of mixed solution: Dissolving poly(3,4-ethylenedioxythiophene) and poly(styrene sulfonic acid) in a mass ratio of 1:1 in acetonitrile to prepare a conductive polymer solution with a concentration of 5-10wt%, dispersing nano copper powder in the solution to form a copper powder suspension, wherein the mass ratio of nano copper powder to deionized water in the copper powder suspension is 1:(15-30), and fully stirring the conductive polymer solution and the copper powder suspension in a volume ratio of 1:(1-2) to obtain a mixed solution; S2. Preparation of polymer / copper powder core microspheres: The mixed solution is placed in an ultrasonic atomizer, and the solution is atomized into tiny droplets by the action of ultrasound to form polymer / copper powder mixed core microspheres, wherein the ultrasonic spraying conditions are as follows: temperature 45-55° C., time 10-15 min, power 100-110 W, and the polymer / copper powder mixed core microspheres are prepared after complete drying and curing; S3, activation treatment: The prepared polymer / copper powder mixed core microspheres are finely polished, then rinsed with distilled water, and then placed in a constant temperature alkaline washing solution of 55°C, taken out after 3-5 minutes and rinsed with distilled water to obtain a deoiled solid A; solid A is placed in an acid solution and soaked for 40-60 seconds, and then rinsed with distilled water to obtain an acid-washed solid B; solid B is placed in an activation solution for 5 minutes to obtain a surface-activated polymer / copper powder mixed core microsphere, wherein the concentration of potassium phosphate in the activation solution is 110 g / L, the concentration of phosphoric acid is 100 mg / L, the concentration of sodium fluoride is 20 g / L, and the concentration of sodium dodecyl sulfate is 100 mg / L; S4, polymer / copper powder core microsphere surface treatment: S4.1, immersing the surface activated polymer / copper powder mixed core microspheres in a plating solution A containing nickel ions, and electroplating to form a nickel layer on the surface of the microspheres, wherein the nickel ion concentration in the plating solution A is 20-25 g / L, the boric acid concentration is 20-25 g / L, and the hypophosphite ion concentration is 8-12 g / L; S4.2, continue to immerse the polymer / copper powder core microspheres obtained in step S4.1 into the electroplating solution B containing silver ions at a current density of 1 to 10 A / dm 2 A silver layer is formed by electroplating under the conditions of S4.3, immerse the polymer / copper powder core microspheres obtained in step S4.3 in a solution containing electroplating solution C at a current density of 3 to 5 A / dm 2 A Sn-Ag-Cu alloy layer is formed by electroplating under the conditions of, wherein the concentration of stannous methanesulfonate in the electroplating solution C is 0.2 mol / L, the concentration of copper methanesulfonate is 1.5 mmol / L, the concentration of silver methanesulfonate is 4.5 mmol / L, the concentration of sodium citrate is 0.45 mol / L, the concentration of ethylenediaminetetraacetic acid is 0.375 mol / L, the concentration of ascorbic acid is 1 g / L, the concentration of thiourea is 0.6 mol / L, the concentration of modified graphene is 0.2-0.5 g / L, and the concentration of the dispersant is 10-20 g / L; S5. Cleaning and drying: The electroplated polymer / copper powder core microspheres were washed with deionized water and dried at 105° C. for 8 to 14 hours to prepare polymer copper powder mixed core solder balls.

2. The method for preparing a polymer copper powder mixed core solder ball according to claim 1, characterized in that: In step S3, the constant temperature alkaline washing solution comprises NaOH, sodium carbonate, sodium phosphate and pure water in a mass ratio of 3:1:3:

50.

3. The method for preparing a polymer copper powder mixed core solder ball according to claim 1, characterized in that: In step S3, the acid solution is a nitric acid solution with a concentration of 30 ml / L.

4. The method for preparing a polymer copper powder mixed core solder ball according to claim 1, characterized in that: In step S4.1, the current density during electroplating is 3 to 7 A / dm 2 The electroplating time is 5 to 10 minutes and the temperature is 25 to 50°C.

5. The method for preparing a polymer copper powder mixed core solder ball according to claim 1, characterized in that: In step S4.2, the silver ion concentration in the electroplating solution B is 10-15 g / L, and the boric acid concentration is 20-30 g / L.

6. The method for preparing a polymer copper powder mixed core solder ball according to claim 1, characterized in that: In step S4.2, the electroplating time is 3 to 6 minutes.

7. The method for preparing a polymer copper powder mixed core solder ball according to claim 1, characterized in that: In step S4.3, the preparation process of the modified graphene is as follows: At 40-45° C., graphene, N-ethylpyridinium tetrafluoroborate and ethanol in a mass ratio of (1-3): (10-15): 50 are uniformly mixed, and ultrasonic treatment is performed for 35-50 minutes. After the ultrasonic treatment, the precipitate is centrifuged and washed with deionized water, and vacuum dried at 95° C. for 6-10 hours to obtain modified graphene.

8. The method for preparing a polymer copper powder mixed core solder ball according to claim 1, characterized in that: In step S4.3, the dispersant is cetearyl alcohol polyether and sodium hexadecyl sulfate in a mass ratio of 1:

1.

9. The method for preparing a polymer copper powder mixed core solder ball according to claim 1, characterized in that: In step S4.3, the current density during electroplating is 2.5 to 3.5 A / dm 2 The electroplating time is 3 to 5 minutes and the temperature is 25 to 40°C.

10. An application of the polymer copper powder mixed core solder ball as claimed in any one of claims 1 to 9, characterized in that: The polymer copper powder mixed core solder ball can be applied to traditional soldering technology and the field of electronic device packaging.